2018
DOI: 10.5694/mja18.00241
|View full text |Cite
|
Sign up to set email alerts
|

Chronic idiopathic constipation in adults: epidemiology, pathophysiology, diagnosis and clinical management

Abstract: Chronic idiopathic constipation (CIC) is one of the most common gastrointestinal disorders, with a global prevalence of 14%. It is commoner in women and its prevalence increases with age. There are three subtypes of CIC: dyssynergic defaecation, slow transit constipation and normal transit constipation, which is the most common subtype. Clinical assessment of the patient with constipation requires careful history taking, in order to identify any red flag symptoms that would necessitate further investigation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
155
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(158 citation statements)
references
References 90 publications
(151 reference statements)
1
155
1
1
Order By: Relevance
“…The differences in the prescription patterns of laxatives are possibly due to the inclusion or absence of these medications in the health systems of different countries. For example, bisacodyl is only found in the health benefits plan in Colombia [11], which would explain the increased use of stimulant laxatives in the country; stimulant laxatives are indicated for patients who do not respond to osmotic laxatives [2,5,21,22]. Constipation is a pathology caused by multiple factors, including physiological changes in the intestine associated with age, comorbidities, consumption of certain medications, loss of mobility, and inadequate diet [14].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the prescription patterns of laxatives are possibly due to the inclusion or absence of these medications in the health systems of different countries. For example, bisacodyl is only found in the health benefits plan in Colombia [11], which would explain the increased use of stimulant laxatives in the country; stimulant laxatives are indicated for patients who do not respond to osmotic laxatives [2,5,21,22]. Constipation is a pathology caused by multiple factors, including physiological changes in the intestine associated with age, comorbidities, consumption of certain medications, loss of mobility, and inadequate diet [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we did not measure other factors, such as existing diseases, medication consumption, fluid and dietary fiber intakes, and physical activity, which are important factors that contribute to chronic constipation in older people. 1,2,17,20…”
Section: Discussionmentioning
confidence: 99%
“…Chronic constipation is common, but studies among older people are limited, especially in Southeast Asian countries. 1,2 Several studies have reported a wide variation in the prevalence of chronic constipation among community-dwelling older people, ranging from 16.5% to 75% of the population in question. 1,[3][4][5] Nevertheless, a lack of knowledge and understanding among older people of the symptoms may result in under-or overreporting of its occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the past, CIC and IBS-C were considered separate and distinct disorders; however, these disorders often coexist in patients and, because symptoms wax and wane over time, can be difficult to differentiate in routine clinical practice. 4 Furthermore, Rome IV criteria support the emerging concept of CIC and IBS-C as a continuous spectrum of disorders with overlapping symptoms. 3 Prosecretory agents are efficacious in the treatment of CIC and IBS-C; however, data are limited regarding the safety and efficacy of these agents for the treatment of constipation in elderly populations.…”
Section: Introductionmentioning
confidence: 93%